Traumák kimutatásának kísérlete a Lett Ortodox Egyház hivatalos dokumentumaiból egyház és ünnep kulcsszavak szoftveres eredményei - Wimmer Krisztina; Móra Kárpát-medencei Interdiszciplináris Szakkollégiumi Konferencia (6.) (2022) (Szeged) (Szegedi Tudományegyetem Móra Ferenc Szakkollégiuma Szeged, 2023)
The study is concerned with testing the theory of Wounded Collective Identity that focuses on the trauma of the Central and Eastern European region. The qualitative research using an interdisciplinary approach on official documents of the Latvian Orthodox Church seeks to answer the question, how trauma can be detected from the corpus by using keyword searches? The tests are based on deductive approach of previous research, which relies on the WCI63 theory. I run the tests in ATLAS.ti Qualitative Data Analysis software and use the most frequent keywords „church” and „holiday”, I illustrate the analytical possibilities of the results obtained (noun-adjective relations, context analysis with sentences) and investigate the applicability of these two keywords. In the case of the keyword „church”, I argue that there is no need for a large number of codes representing the ecclesiastical sphere, since the focus of the analysis is on ecclesiastical documents anyway. The large number of results for the „holiday” keyword also seems to support the theoretical framework’s claim that commemorations and references to past historical traumas are foregrounded during holidays. However, the keyword analysis shows that the majority of the documents focus on church holidays, and the use of the keyword „holiday” alone is not sufficient to reveal the investigated traumas. The solution for detecting trauma may be the use of the keyword „church” in combination with other keywords, which will be the subject of a forthcoming study.
Keywords: Társadalomtudományok; Politikatudomány; Bölcsészettudományok; Filozófia, etika és vallástudományok